A review of therapy-related myelodysplastic syndromes and acute myeloid leukaemia (t-MDS/AML) in Irish patients: a single centre experience. Issue 6 (3rd July 2017) - Maung, Su W.; Burke, Cathie; Hayde, Jennifer; Walshe, Janice; McDermott, Ray; Desmond, Ronan; McHugh, Johnny; Enright, Helen
ABSTRACT: Objectives: To demonstrate the incidence, characteristics, treatment and outcomes of patients with therapy-related myelodysplastic syndromes and therapy-related acute myeloid leukaemia (t-MDS/AML) in a tertiary referral centre. Methods: Patients meeting the diagnostic criteria for t-MDS/AML from 2003 to 2014 were reviewed to analyse their diagnostic features, details of antecedent disorder and treatment, approach to management and survival. Results: 39 patients who developed t-MDS/AML were identified with incidence of 8.7%. Median age and gender distribution were similar to de novo MDS but t-MDS/AML patients had greater degree of cytopenia and adverse karyotypes. Time to development of t-MDS/AML was shortest for patients with antecedent haematological malignancy compared to solid tumours and autoimmune disorders (46, 85 and 109 months). Patients with prior acute leukaemia had the shortest latency and poor overall survival. Treatment options included best supportive care (56%), Azacitidine (31%) or intensive chemotherapy/allogeneic transplant (13%). Median OS of all patients was 14 months. Survival declined markedly after two years and 5-year OS was 13.8%. Longer survival was associated with blast count <5% at diagnosis, previous haematological disorder, lower risk IPSS-R and a normal karyotype. Four out of five patients who received intensive therapy/transplant remain alive with median OS of 14 months. Median OS of Azacitidine-treated group was 11 months. Discussion: t-MDS/AML patients showed unique characteristics which influenced their treatment and outcomes. IPSS-R may be useful in risk-adapted treatment approaches and can predict outcomes. Survival remains poor but improved outcomes were seen with allogeneic transplantation. Azacitidine may be effective in patients unfit for intensive therapies.